Menumbuhkan Jiwa Wirausaha Sejak Dini Melalui Pengenalan Kewirausahaan pada Panti Asuhan Al Ikhlas - Huzaemah Huzaemah; Yuliana Yuliana; Muhammad Umar; Santi Rahmawaty; Mutia Sholeha; Maryani Maryani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This Community Service Activity (PKM) aims to foster an entrepreneurial spirit from an early age through entrepreneurial literacy in the children of the Al Ikhlas Orphanage in Palu, Central Sulawesi. Entrepreneurial literacy is considered important to equip foster children with knowledge and skills that can support their independence, both financially and psychologically, after leaving the orphanage. Methods for implementing this activity include an introduction to entrepreneurship, providing motivation, practical business idea development sessions, business simulations, and interactive discussions. Evaluation shows that this activity received a positive response from orphanage children and administrators, which encourages the continuation of similar programs in the future. It is hoped that the results of this activity will have a significant impact in preparing the younger generation to be independent and economically productive.